Correlation between sCTLA-4 and sCD86 Levels with Disease Activity of SystemicLupus Erythematosus (SLE) Patients Based on SLEDAI Score - Helsa Eldatarina (Indonesian Journal of Rheumatology, 2024)
Background. Systemic Lupus Erythematosus (SLE) is an autoimmunedisease with multisystem involvement which arises from multifactorialcauses. Continuous exposure to autoantigens and chronic activation of theimmune system, especially memory T lymphocytes, contribute to prematureimmunosenescence. sCTLA-4 and sCD86 are soluble costimulatorymolecules of CTLA-4 and CD86, which play a role in the occurrence ofimmunosenescence in SLE. The presence of immunosenescence will causehigher morbidity and mortality. This research was conducted to establishthe correlation between the increased levels of sCTLA-4 and sCD86 and theseverity of SLE, as measured by the SLE Disease Activity Index (SLEDAI)score. Methods. This analytical observational research utilized a crosssectional approach involving 35 female SLE patients diagnosed according to the SLICC 2012 criteria. SLE disease activity was measured using SLEDAI score. Serum sCTLA-4 and sCD86 levels were measured using the ELISA method. Statistical analysis was conducted using the Mann-Whitney test for comparisons and the Spearman test for correlation analysis, with a significance level of p<0.05. Results. sCTLA-4 levels were higher and significantly different in patients with moderate SLE (p=<0.001; p<0.05), and there was no significant difference in sCD86 levels (p=0.915; p>0.05).Increased sCTLA-4 levels were positively correlated with the severity of SLE(r =0.361, p=0.033), while no significant correlation was observed in sCD86levels (r=-0.094, p=0.591). Conclusion. Elevated sCTLA-4 levels werepositively correlated with increased severity of SLE based on the SLEDAIscore.